Facilities Of Learning Physical Education, In Biringkanayya City Of Makassar - Ferawati (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2020)
The availability of adequate learning facilities and infrastructure can optimize the ability of a teacher to support an effective and efficient learning process in physical education learning. The aim is to describe the state of the Vocational High School Physical Education facilities and infrastructure in Biringkanaya District, Makassar City. This research is a descriptive study with a survey method. The research sample was 8 schools. Based on the results of the study, it can be concluded that the facilities and infrastructure for health and physical education in Vocational High Schools throughout the Biringkanaya District, Makassar City, there are 2 schools that are in the very good category with a percentage of 25%, 1 school is in the good category with a percentage of 12.5%. , in the medium category 3 schools with a percentage gain of 37.5%, and in the poor category 2 schools with a percentage of 25.0%, and no school was in the very poor category.